Assessment of the prevalence of stress, anxiety and depression in healthcare workers providing services related to communicable diseases in primary-level health units in Maputo city, Mozambique: an observational cross-sectional study protocol - Tavares Madede; Mariano Joaquim Creyghton Pedro (BMJ Open)
Introduction Mental health is essential for well-being and critical to the quality of care delivered by healthcare professionals. Health workers face increased risks of mental health disorders due to long hours, high emotional and physical demands, and exposure to communicable diseases, which exacerbate stress and anxiety levels. Evidence from low-income countries, including Mozambique, is scarce, yet health professionals in these regions frequently deal with the dual burden of communicable diseases and resource constraints. This study addresses a critical evidence gap by focusing on the mental health of healthcare professionals in Mozambique who are frequently exposed to psychological stress while managing communicable diseases. It aims to assess the prevalence of stress, anxiety and depression among healthcare workers providing services related to communicable diseases in primary-level health units (PHUs) in Maputo City, Mozambique. The study also seeks to identify personal and professional factors associated with these mental health disorders.Methods and analysis This is an observational cross-sectional study targeting healthcare workers in PHUs who provide services related to communicable diseases in Maputo City. Using convenience sampling, 382 participants will be recruited, stratified by health unit type. This sample size was calculated manually using the formula by Wang and Ji (2020). Data will be collected through a questionnaire, including demographic and professional information and a validated tool (Depression, Anxiety and Stress Scale, DASS-21), using the Research Electronic Data Capture (REDCap) Software for secure data capture. Descriptive and inferential statistical analyses will be performed using IBM SPSS Statistics to estimate prevalence rates and explore associated factors.Ethics and dissemination The study was approved by the Interinstitutional Committee on Bioethics in Health of the Faculty of Medicine/Maputo Central Hospital (CIBS FM&HCM/117/2024). Written informed consent will be obtained, and participants experiencing significant discomfort will be referred for mental health support. Findings will be disseminated via academic theses, peer-reviewed publications, national conferences, and reports shared with the Ministry of Health to inform mental health interventions for healthcare workers.Registration This protocol is registered with the Interinstitutional Committee on Bioethics in Health of the Faculty of Medicine/Maputo Central Hospital (CIBS FM&HCM).